Early weaning damages the intestinal epithelial barrier of squabs through toll-like receptor signaling pathways - Qianqian Xu; Mengqi Lv; Yiwei Yuan; Tianliang Ling; Xiaoting Zou; Xinyang Dong (Poultry Science)
ABSTRACT: Stress damage caused by early weaning and its possible mechanism have been studied mainly in young mammals, but rarely in altrices, especially in squabs. The study aimed to investigate the possible molecular mechanism of intestinal epithelial barrier damage caused by early weaning in squabs through determining the intestinal permeability, the ultrastructure of villous epithelium, the contents of ileal cytokines, and the protein relative expression of tight-junction proteins, TLRs and their mediated key factors in inflammatory signaling pathways. A total of 192 newly hatched squabs were randomly divided into 2 groups, 1 group was weaned and fed artificial pigeon milk from d 7, and the other group continued to be fed by the parent pigeons. The ileal mucosa and serum of 8 replicates were collected at 1, 4, 7, 10, and 14 d after weaning. The results indicated that early weaning could reduce the growth performance of squabs and damage the intestinal epithelial barrier, which is characterized by down-regulating the protein expression of claudin-1/3, up-regulating the protein expression of claudin-2, promoting the secretion of pro-inflammatory factors, inhibiting the secretion of anti-inflammatory factors, and increasing the permeability of the intestinal barrier. The specific mechanism of stress damage might be the activation of TLR2/4-MyD88-ERK/JNK inflammatory signaling pathway leading to the increase levels of IL-6 and TNF-α.